English instructors' professional development need areas and predictors of professional development needs - EKŞİ, GÜL (ELSEVIER SCIENCE BV, 2013)
This study aimed to identify English instructors' professional development needs and to examine the role of years of teaching experience, workload, department of graduation, and instructors' perceptions of professional development programs in predicting professional development needs. The instructors were asked to indicate their degree of need in various areas of professional development via a questionnaire. The total scores for each area were calculated to identify the areas in which the degree of need was the highest and lowest. The results showed that the highest degree of need was New theories and practices of ELT, followed by Use of technology in ELT. Teachers' degree of need was lowest in Lesson planning and Classroom management. The results indicated that only length of teaching experience was significant in predicting professional development needs. (C ) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of ALSC 2012
Keywords: ELT; Professional developmet; Professional development need areas; Predictors of professional development needs